HEGEMONI BUDAYA POP: BUDAYA BALI TERKOMODIFIKASI - I Putu Yogantara; I Nyoman Rediasa; I Wayan Sudiarta (Jurnal Pendidikan Seni Rupa Undiksha, 2026)
This research explores the phenomenon of popular culture hegemony that triggers a systematic commodification process of Balinese culture in the postmodern era. Bali, renowned for the nobility of its local wisdom, currently faces major challenges in the form of cultural clashes due to the dominance of global influences that prioritize visual-commercial aspects over fundamental values. This hegemony causes Balinese culture to be frequently repackaged into commodities that are marketable and "Instagrammable" to meet global market demands. Through the Design and Development (D&D) method, the author created interactive intermedia artworks titled "Lost Paradise" and "Antara Mengikuti dan Diikuti". These works utilize the assemblage technique by integrating found objects and sensor technology as a medium for sociocultural reflection. The results of the creation demonstrate that interactive art can act as a critical instrument involving the active participation of the audience to reflect on their position amidst the currents of modernity. This work concludes that the effort to preserve the essence of local culture amidst the pressure of global hegemony is the collective responsibility of every individual. Keywords: Pop Culture Hegemony, Commodification of Balinese Culture, Intermedia Art, Assemblage Art, Interactive Art.